THE USE OF DIGITAL STORYTELLING NARRATIVE TEXT TO IMPROVE STUDENTS SPEAKING ABILITY AT GRADE TEN SMAN 2 BANDAR LAMPUNG - Mila Febriyanti; Susanto Susanto (LINGUISTIKA, 2017)
This qualitative of this research aim at describing the use of digital storytelling narrative text to improve students speaking ability at grade ten in Sekolah Menengah Atas Negeri Bandar Lampung academic year 2017/2018 by using some instruments such as observation, questionare and speaking test. Based on experience of almost all students at grade ten in Sekolah Menengah Atas Negeri 2 Bandar Lampung has not used digital storytelling therefore the teacher as facilitator provides this one good media which is digital storytelling. Digital storytelling is effective to improve on speaking ability. It is proved that the students became more confident, they speak fluently, the students also produce more correct sentences, correct pronunciation, and more vocabularies. The result of this research show there is an increase of students respond, motivation, and interest in the learning process using digital storytelling. It is concluded that the used of digital storytelling narrative text can improve students’ speaking ability at grade ten of SMA N 2 Bandar Lampung. The implementation of using digital storytelling improves students speaking ability.